Hypoglycemic and Antioxidant Activity of the Residual Aqueous Extract of Tamarindus Indica - Musa, Yerima; A., Samaila (International Journal of Pharmacological Research, 2018)
Introduction: The harmful effect of oxidative stress to cells of all aerobic organisms due to the high reactivity of the species can no longer be overemphasized. Reactive Oxygen Species are free radicals because the molecules have a lone electron in the outer shell. Tamarindus indica Linn, belongs to the Dicotyledonous family Leguminosae Sub Family Caesalpiniaceae, which is the third largest family of flowering plants. Aim: The current study is aimed at determining the hypoglycemic effect and the free radical scavenging activity of residual aqueous extract of T. indica. Methodology: The oral median lethal dose (LD50) of the RAF in rats was conducted according to the method of Lorke (1983). Hyperglycaemia was induced by a single intraperitoneal injection of 150 mg/kg body weight of alloxan to 12 hours fasted rats. Hydrogen peroxide scavenging activity, reducing power assay and Free radical scavenging activity of the fraction was investigated. Results: The residual aqueous fraction of the extract at doses used significantly (p 0.02) lowered the Blood Glucose Level (BGL) with the 500 and 250 mg/kg doses in the first hour. At the eighth hour 250 mg/kg of the extract significantly (p 0.02) lowered the BGL. Graded concentrations of the extract used showed a dose depended increase in the antioxidant activity using the hydrogen peroxide scavenging activity and reducing power assay. The DPPH antioxidant activity of the fraction was estimated from the absorbance of the free radical. Conclusion: The results showed a concentration dependent percent scavenging antioxidant activity.